Assessing Effects of Multi-Scale Landscape Pattern and Habitats Attributes on Taxonomic and Functional Diversity of Urban River Birds - Qian Mao; Jianxin Sun; Yuanyuan Deng; Zhaolu Wu; Haotian Bai (Diversity, 2023)
Several studies have revealed that urban rivers with relatively complete habitat structures can support a high level of biodiversity in urban areas. However, few studies have analyzed the impact of the plan, design, and management of multi-scale urban riverside green space on bird communities by assessing several aspects of diversity (e.g., taxonomic and functional). In this study, we explored bird community variation (taxonomic and functional) among three rivers (28 sampling sites) with different levels of human disturbance along the urban development gradient in Kunming, Yunnan Province, China, during an annual cycle. This study related bird species richness and functional diversity to environmental variables at three spatial scales: landscape metrics at two different landscape scales (500 and 100 m radius) and vegetation structure at patch scales (20 m radius). Using partial least squares regression (PLSR) and multiple linear regression, we found that bird species richness and functional diversity were strongly related to various landscape- and patch-level variables. Multiple linear regression models revealed that, compared with the richness influenced by explanatory variables on three spatial scales (500, 100, and 20 m), the functional diversity was significantly influenced by explanatory variables on the 100 and 20 m scales. Tree cover at the 20 m scale had significantly positive impacts on bird species richness and functional diversity. Forest land in the 100 m scale had a significantly positive effect on bird species richness and functional diversity, while construction land in the two landscape scales (the 500- and 100 m scales) had a significantly negative effect on species richness. Accordingly, we suggest that urban riverside green space should be planned and managed at multiple scales.